Gregorio Salvador, teacher, scholar and sabe: In memoriam - Regueiro Rodríguez, María Luisa (Razón y fe, 2021)
The article evokes the figure, life and work of Gregorio Salvador, Academician of the Royal Spanish Academy, as well as his career as dialectologist and founder of the Semantic School. Salvador, master of Lexicography, profound connoisseur of the linguistic reality of Spanish in the world, with extensive production in the media, has been the recipient of awards and distinctions of special relevance. The article closes with the Romance de mi padre by his daughter poet Aurora Salvador, so far unpublished.
Keywords: Gregorio Salvador; RAE; philological work; dialectology; semantics; lexicography